(untitled) (Global Journal of Science Frontier Research, 2015)
This short note aims to offer the conceptual approach to the definition of the mean value, with reection to the prewious very interesting attempts with the same goal. The definition is at once simple and powerfull and its advantage are demonstrated with aplications in financial mathematics. The definition of the man value involves the term objective function, which characterize the nature of object, which is taken to average.